PERANCANGAN KARBURATOR UNTUK BAHAN BAKAR BIOGAS PADA GENERATOR SET 900 VA - , EFENDI S WIRATERUNA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Biogasis arenewableenergysourcethat is environmentally-friendly andwidely usedin rural areasforcooking assubstitute ofLPG. The utilization ofbiogascan be advanced as a source ofelectrical energy in rural area. Therefore, generatorsets with gasoline fuel needs to be modified so that generator set can operate withthe fuel of biogas. GeneratorsetsME1800EXismodified on its carburetor with3variationsof the biogas inletatthe venturithroat that has variations of 1, 2, and 3 biogas inlet.Eachinlethasthe samecross-sectional areawith diameter 4mm. The performance of biogas generator sets is measuredby givingload until800Wfor eachvariation ofthe biogas inlet. The primary data for performance of generator sets are frequency, current,andvoltage. The secondary data for performance of generator sets is the power. Result ofresearch showthat thegeneratorsetcan operate in all thevariations ofbiogas inlet. Result of experiment show that the carburetor with 3 orifice of biogas inlet and ratio of cross-sectional area 1 : 3.5 produce the best performance. Generator set can accept load until 700 W with the real power produced 713.87 VA. The average value of spesific fuel consumption is 4,200liter/kWh. Comparison between a performance of generator set using gasoline and biogas show that the performance of generator set occur discharge. The power of generator set become 86.31 % at the carburetor in 3 orifice of biogas inlet.